Selective modulation by PARP-1 of HIF-1α-recruitment to chromatin during hypoxia is required for tumor adaptation to hypoxic conditions - Martí, JM; Garcia-Diaz, A; Delgado-Bellido, D; O'Valle, F; González-Flores, A; Carlevaris, O; Rodríguez-Vargas, JM; Amé, JC; Dantzer, F; King, GL; Dziedzic, K; Berra, E; et al. (Elsevier, 2021)
BACKGROUND: The adaptation to hypoxia is mainly controlled by the HIF transcription factors. Increased expression/activity of HIF-1α correlates with poor prognosis in cancer patients. PARP-1 inhibitors are used in the clinic to treat BRCAness breast/ovarian cancer and have been shown to regulate the hypoxic response; therefore, their use could be expanded. METHODS: In this work by integrating molecular/cell biology approaches, genome-wide ChIP-seq, and patient samples, we elucidate the extent to which PARP-1 exerts control over HIF-1-regulated genes. RESULTS: In human melanoma, PARP-1 and HIF-1α expression are strongly associated. In response to a hypoxic challenge poly(ADP-ribose) (PAR) is synthesized, HIF-1α is post-transcriptionally modified (PTM) and stabilized by PARylation at specific K/R residues located at its C-terminus. Using an unbiased ChIP-seq approach we demonstrate that PARP-1 dictates hypoxia-dependent HIF-recruitment to chromatin in a range of HIF-regulated genes while analysis of HIF-binding motifs (RCGTG) reveals a restriction on the recognition of hypoxia responsive elements in the absence of PARP-1. Consequently, the cells are poorly adapted to hypoxia, showing a reduced fitness during hypoxic induction. CONCLUSIONS: These data characterize the fine-tuning regulation by PARP-1/PARylation of HIF activation and suggest that PARP inhibitors might have therapeutic potential against cancer types displaying HIF-1α over-activation.